The Relation Between Compulsive Sexual Behaviors and Aggression in a Substance-Dependent Population. Issue 1 (2nd January 2016) - Elmquist, JoAnna; Shorey, Ryan C.; Anderson, Scott; Stuart, Gregory L.
ABSTRACT: Research supports a high comorbidity between compulsive sexual behaviors (CSBs) and substance use disorders (SUDs), which are both classified by increased impulsivity. Literature has also indicated that increased impulsivity and substance use are associated with aggression. However, no known research has examined the relationship between CSBs and aggression among a substance-dependent population. The purpose of this study was to examine this relationship. Participants included 349 male patients in treatment for SUDs. Results indicated that after controlling for alcohol and drug use and problems and age, CSBs were significantly associated with total aggression, aggressive attitudes, physical aggression, and verbal aggression. This is the first known study to examine this relationship; thus continued research is needed to extend and replicate these findings.